Analisis At-tauriyah dalam Surah At-tahaah Ayat 5 dan Al-irshad dalam Surah Al-luqman Ayat 7 dan 12 - Haikal Eriyanto Marpaung; Putri Nadira Sandra; Harun Alrasyid (Student Research Journal, 2025)
At-tauriyah refers to the use of words or expressions that have two meanings, where the intended meaning is the implied meaning, while the other meaning is the zahir (clear) meaning. The aim is to give a deep impression or play on the meaning to get attention or a certain impression in conversation or writing. For example, using words that can be literally understood in two ways, and the listener or reader needs to understand the implied meaning based on the context of the purpose. At-tauriyah is often used to give the impression of surprise or to convey a hidden message, often with elements of joking, innuendo, or to hide true intentions, while Al-irshad refers to giving clear and direct instructions or advice, in the context of using language that gives direction or guidance to listeners or readers. This method is often used in speeches, lectures, or teaching to guide the audience to understanding. Better or to provide moral advice. A-lirshad aims to guide or provide clear instructions, help other people understand the values or actions that need to be taken based on applicable principles or norms, these two techniques are used in balagah to increase the impression of language in creating deeper meaning or giving direction clear and useful.